Financial Contagion in an Age of COVID-19: On Biological, Human, and Algorithmic Mimesis. Issue 1 (April 2022) - Borch, Christian
Abstract : This article discusses the financial turmoil unleashed by the COVID-19 pandemic in March 2020. It argues that the market mayhem in which prices plummeted cannot be fully explained by real-economic factors such as uncertainty about the future global economy. Instead, I suggest analysing the events as a manifestation of financial contagion in which the mimesis of market participants becomes an independent explanatory force. In making this argument, the article returns to late nineteenth-century ideas about mimesis and social contagion as well as discussions about the collective mimesis – constitutive of a mimetic turn – that may result from social avalanches.